COMMUNICATION APPREHENSION DALAM PROSES PENYELESAIAN SKRIPSI PADA MAHASISWA ILMU KOMUNIKASI UNIVERSITAS MULAWARMAN ANGKATAN 2016 - Samuel Hot Anugrah Simanjuntak Samuel; Rina Juwita (Jurnal Ilmu Komunikasi Balayudha, 2023)
This study aims to find out how communication apprehension is in the process of completing a thesis in communication science students at Mulawarman University class of 2016. This research is a type of qualitative descriptive research with a focus on Internal Discomfort, Avoidance of Communication, Communication Disruption, and Overcommunication. Based on the results of research that has been carried out, communication apprehension experienced by students in completing their thesis is an uncomfortable condition experienced by students and is not permanent, which arises when thinking, discussing or the process of doing the final thesis assignment. This happens because of the management of information and drawing conclusions that exist within oneself which creates a feeling of worry, nervousness and fear in individuals. The characteristics shown by someone when experiencing communication anxiety are different, from the results and discussion of this study 5 informants all experienced internal discomfort characteristics, 2 out of 5 informants showed avoidance of communication, 1 out of 5 informants showed communication disruption characteristics and 1 out of 5 informants showed over communication. Ways to overcome communication anxiety (communication apprehension), there are several ways to reduce communication anxiety. From the results and discussion of this study the way to reduce communication anxiety is to keep thinking positively, taking deep breaths to calm down, looking for diversions and also fighting the source of the anxiety itself.